The ancillary carbon benefits of SO2 reductions from a small-boiler policy in Taiyuan, PRC - Morgenstern, Richard; Zhang, Xuehua; Krupnick, Alan (2004)
Proposals for greenhouse-gas reductions have been met with widespread skepticism in the developing world, in part because such countries find their conventional air-pollution problems more pressing. The goal of this article is to examine whether reductions in carbon emissions that are ancillary to conventional pollutant reductions from a policy to phase out small boilers in down-town Taiyuan, China are large enough to make such policies attractive carbon data, there are significant carbon benefits (on the order of 50% to 95% reduction) associated with this policy, with large reduction potential elsewhere in China. Although the cost for boilers that switched out of coal was almost U.S. $2,900 per ton of SO2 reduced, these ancillary carbon reductions are free from a social perspective. Such initiatives represent a potentially significant source of carbon reductions that developed countries could help pay for, bringing significant health and other benefits to the country. -Reproduced.
Keywords: Air pollution